The Study of Planting Media Water Holding Capacity and Productivity Plants in Potato Cultivation (Solanum tuberosum L.) - Suastika, I Made Nanda; Setiyo, Yohanes; Sulastri, Ni Nyoman (Jurnal BETA (Biosistem dan Teknik Pertanian), 2024)
Since farmers plant potatoes in the dry season, water becomesthe main component for plants to grow well. This study aims to determine the ability of planting media to bind nutrients and the proportion of types of planting media that produce the best water holding capacity (WHC) for potato cultivation productivity. Parameters observed in this study include porosity, plant water availability (KAT), bound water volume (VAT), electrical conductivity (EC), potato productivity. This study used a completely randomized design with 8 levels of composition, 100% chicken manure compost (P1), 100% soil (P2), 100% husk charcoal (P3), 50% soil + 40% chicken manure compost + 10% husk charcoal ( P4), 50% soil + 30% chicken manure compost + 20% husk charcoal (P5), 50% soil + 20% chicken manure compost + 30% husk charcoal (P6), 50% soil + 10% chicken manure compost + charcoal husk 40% (P7), 50% soil + 25% chicken manure compost + 25% husk charcoal (P8). Rice husk charcoal planting medium 100% (P3) produces porosity, water availability for plants and the highest volume of bound water, with a porosity value of 55.71%, a value of water availability for plants 17.22% wb, and a volume value of bound water 1.603 ml..Treatment of 100% soil media (P2) resulted in the ability of the planting medium to bind the highest nutrients with a value of 788.67 S/cm. The proportion of soil 50% chicken manure compost 10% husk charcoal 40% produced the highest productivity of potatocultivation, namely 571.70 g/plant.